Re-emerging outbreaks of chikungunya virus infections of increased severity: A single-center, retrospective analysis of atypical manifestations in hospitalized children during the 2019 outbreak in Bangkok, Thailand - Artchavit Boonanek; Kulkanya Chokephaibulkit; Wanatpreeya Phongsamart; Keswadee Lapphra; Supattra Rungmaitree; Navin Horthongkham; Orasri Wittawatmongkol (PLoS ONE, 2025)
This retrospective observational study assesses the clinical characteristics, atypical manifestations, and treatment outcomes in pediatric patients hospitalized with chikungunya virus (CHIKV) infection during the Bangkok outbreak in 2019. Children <18 years old hospitalized from January 1 to December 31, 2019, and confirmed positive for CHIKV infection by RT-PCR or IgM antibodies were included in this study at a tertiary care center in Bangkok, Thailand. Patient demographics, clinical manifestations, and laboratory findings at the time of hospitalization were collected from de-identified medical records. Of 31 included children, seven (22.6%) were <1 year old, 22 (71.0%) were male, nine (29.0%) had underlying medical conditions, four (17.4%) tested positive for dengue coinfection, and four (12.9%) had multi-organ involvement. The median age was 9.5 (IQR 6.9–12.5) years. Most (90.3%) had atypical clinical manifestations, four (12.9%) had life-threatening manifestations. Two (6.5%) neonates had congenital CHIKV. The most common manifestations included fever (100.0%), rashes (77.4%), myalgia (41.9%), and arthralgia (35.5%). The three most involved organ systems presenting atypical manifestations included gastrointestinal (32.3%), dermatologic (32.3%), and neurological (22.6%) systems. Of those with dermatologic involvement, 67.7% had maculopapular rashes, 19.4% bullous skin lesions, and 6.5% generalized erythroderma. At the time of presentation, 25 (80.6%) children had lymphopenia, five (16.1%) had anemia, and none had thrombocytopenia. Five (16.1%) children required intensive care and four (12.9%) developed shock. Thirteen (41.9%) children, five with neurological involvement, fully recovered at discharge. Among the remaining children, five (16.1%) still had musculoskeletal conditions, 11 (35.5%) had skin lesions, and two (6.5%) with congenital CHIKV had skin lesions and neurological sequelae. Despite the small cohort, the observed frequency of neurological complications attributed to CHIKV infection justifies long-term follow-up in children with neurological manifestations and complications. CHIKV should be suspected in endemic countries and tested for in febrile children, particularly those with rash and neurological involvement.